Moralitas Bisnis dalam Al-Qur’an Analisis Surat Al-Furqan Ayat 57-59 - Deswita Lestari Btr; Ferizal Ferizal; Indah Amelia; Muhammad Alfin; Nabila Nabila (Jurnal Budi Pekerti Agama Islam, 2025)
Many Muslim communities still consider business ethics to be unimportant in business activities, because business is nothing more than just seeking profit. This study will discuss how business ethics are in the perspective of the Qur'an. This study includes library research, namely research that examines data sourced from library materials, using the thematic interpretation method. This study is based on the interpretation of verses of the Qur'an that directly discuss business morality and verses that do not directly discuss business morality. Business in the Qur'an is both material and immaterial. Where business in the Qur'an does not only prioritize material profit but also spiritual profit. The existence of business morality cannot be separated from the business itself. The business morality of the Qur'an contains basic business values ​​such as the values ​​of unity, balance, free will, accountability, and ihsan. Then it gives birth to business morality which is free from elements of falsehood, damage and injustice such as usury, fraud, reducing the measure or fraud, corruption, bribery, gambling, gharar and hoarding and so on. Then business in the Qur'an highly prioritizes hasanah values ​​such as honesty, trustworthiness, fairness, social responsibility, istiqomah, tolerance and friendliness in business life. Thus, business ethics in the Qur'an are not only oriented towards fulfilling the needs and welfare of life in the world, but also business as a means of goodness for safety in the hereafter.